2021
DOI: 10.1002/rra.3870
|View full text |Cite
|
Sign up to set email alerts
|

River water temperatures are higher during lower flows after accounting for meteorological variability

Abstract: River water temperature is known to be important for water quality and ecosystem processes. We quantified the degree to which lower river flows are associated with warmer river water, after accounting for seasonality and meteorological variability.We applied a systematic methodology to analyse observed mean daily river water temperature and mean daily river flow from 47 sites draining mountain, hill, and lowland catchments across the Canterbury region of Aotearoa New Zealand. We fitted regression models to rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 100 publications
1
5
0
Order By: Relevance
“…For instance, Folegot et al (2018) experimentally simulated drought conditions using outdoor flow-through flumes and reported those containing severely depleted water volumes exhibited a maximum warming of 3.3 C, $2 C higher than those conveying higher discharges. In New Zealand, Booker and Whitehead (2022) reported that declines in river flow from the median to the fifth percentile facilitated an average T w increased by 0.5 C, and similar findings have been reported elsewhere in Cfb climates (e.g., Van Vliet et al, 2011).…”
Section: The Influences Of Water Source Contribution On River Water T...supporting
confidence: 80%
“…For instance, Folegot et al (2018) experimentally simulated drought conditions using outdoor flow-through flumes and reported those containing severely depleted water volumes exhibited a maximum warming of 3.3 C, $2 C higher than those conveying higher discharges. In New Zealand, Booker and Whitehead (2022) reported that declines in river flow from the median to the fifth percentile facilitated an average T w increased by 0.5 C, and similar findings have been reported elsewhere in Cfb climates (e.g., Van Vliet et al, 2011).…”
Section: The Influences Of Water Source Contribution On River Water T...supporting
confidence: 80%
“…The cooler T w under higher Q could be partly explained in terms of snowmelt-driven high flows that bring cooler water to the rivers. On the other hand, the warmer T w under lower Q has been documented by previous studies (e.g., Booker & Whitehead, 2021;Woltemade & Hawkins, 2016) and attributed to greater temperature change per unit of heat exchanged with the reduced mass of water, which may be enhanced by heat accumulation due to reduced surface area and flow velocity (Booker & Whitehead, 2021).…”
Section: T W T a And Q Relationshipsmentioning
confidence: 55%
“…After the construction of a reservoir, thermal stratification can occur in the water body, causing the discharge water temperature (DWT) to deviate from the natural water temperature (Ren et al, 2019). Due to the crucial role of water temperature in water quality and aquatic ecosystem processes (Booker and Whitehead, 2022), DWT fluctuations may have adverse effects on downstream aquatic ecosystems (Lu et al, 2023). Therefore, DWT prediction and control is currently a topic of concern for reservoir managers.…”
Section: Introductionmentioning
confidence: 99%